Macro-kinetic model for CuO–ZnO–ZrO2@SAPO-11 core-shell catalyst in the direct synthesis of DME from CO/CO2. (May 2021) - Ateka, Ainara; Portillo, Ander; Sánchez-Contador, Miguel; Bilbao, Javier; Aguayo, Andres T.
Abstract: An original kinetic model has been used to describe the performance of an original CuO–ZnO–ZrO2 @SAPO-11 bifunctional catalyst on the one-stage synthesis of dimethyl ether (DME) from CO/CO2 hydrogenation. The model considers that certain individual reactions (the synthesis of methanol and the reverse water gas shift) occur in the metallic function (core) of the catalyst particle, whereas others (methanol dehydration) take place in the shell (acid function), and that the progress of these reactions is conditioned by the diffusion of the components. The kinetic parameters of the individual reactions and the deactivation kinetics have been calculated from experimental data obtained in a wide conditions range (H2 /COx ratio, 2.5–4; CO2 /COx ratio, 0–1; 10–50 bar; 250–325 °C; 1.25–20 g h molC −1 ). The use of the model for simulating the packed bed reactor has allowed evaluating the influence of the reaction conditions, as well as assessing the effect of the catalysts particle size. The model predicts DME yields of 64% for syngas (H2 +CO) feeds, 38% for CO2 /COx ratio of 0.50 and 17% for H2 /CO2, respectively, at 70 bar and 290 °C. The maximum conversion of CO2 predicted by the model for the same space time value and temperature surpasses 30% for H2 +CO2 feedstocks at 70 bar, greater than the experimental value obtained at 50 bar at the same temperature (∼25%). Graphical abstract: Image 1 Highlights: Components diffusion influence on the catalytic reaction progress is considered. A kinetic model is proposed for describing the performance of core-shell catalysts. The model considers separation of the reactions in the catalyst particle regions. The model is assessed in the direct synthesis of DME using CuO–ZnO–ZrO2 @SAPO-11. The model allows simulating catalytic processes over bifunctional CS catalysts.